Short signature based on factoring problem in the standard model - WANG Zhi-wei1; ZHANG Wei1 (Tongxin xuebao)
A short signature scheme based on factoring problem in the standard model was proposed.To design this sig-nature scheme,the generic construction of fully-secure signatures from weakly-secure signatures and a chameleon hash were employed.A signature in this scheme was compromised of one element in,and the public key was short,requir-ing only the modulus N,one element of,one integer and one pseudorandom function seed.Compared with Hohen-berger’s RSA scheme（Crypto 09）,the computaional cost of the sign algorithm and verification algorithm in this scheme is also much lower.